A Critical Review on The Job Creation Omnibus Law-Forming Process - Bobi Yusuf Noor Fajar; Zaid Zaid (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
This study aims to conduct a critical study of the process of formulating the